SGLT-2 (Sodium-Glucose Cotransporter 2) Inhibition Reduces Ang II (Angiotensin II)–Induced Dissecting Abdominal Aortic Aneurysm in ApoE (Apolipoprotein E) Knockout Mice. Issue 8 (August 2019) - Ortega, Rebeca; Collado, Aida; Selles, Francisca; Gonzalez-Navarro, Herminia; Sanz, Maria-Jesus; Real, José T.; Piqueras, Laura
Abstract : Objective: Abdominal aortic aneurysm (AAA) is a pathological condition of permanent vessel dilatation that predisposes to the potentially fatal consequence of aortic rupture. SGLT-2 (sodium-glucose cotransporter 2) inhibitors have emerged as powerful pharmacological tools for type 2 diabetes mellitus treatment. Beyond their glucose-lowering effects, recent studies have shown that SGLT-2 inhibitors reduce cardiovascular events and have beneficial effects on several vascular diseases such as atherosclerosis; however, the potential effects of SGLT-2 inhibition on AAA remain unknown. This study evaluates the effect of oral chronic treatment with empagliflozin—an SGLT-2 inhibitor—on dissecting AAA induced by Ang II (angiotensin II) infusion in apoE (apolipoprotein E) −/ − mice. Approach and Results: Empagliflozin treatment significantly reduced the Ang II–induced increase in maximal suprarenal aortic diameter in apoE −/ − mice independently of blood pressure effects. Immunohistochemistry analysis revealed that empagliflozin diminished Ang II–induced elastin degradation, neovessel formation, and macrophage infiltration at the AAA lesion. Furthermore, Ang II infusion resulted in a marked increase in the expression of chemokines (CCL-2 [chemokine (C-C motif) ligand 2] and CCL-5 [chemokine (C-C motif) ligand 5]), VEGF (vascular endothelial growth factor), and MMP (matrix metalloproteinase)-2 and MMP-9 in suprarenal aortic walls of apoE −/ − mice, and all were reduced by empagliflozin cotreatment. Western blot analysis revealed that p38 MAPK (p38 mitogen-activated protein kinase) and NF-κB (nuclear factor-κB) activation was also reduced in the suprarenal aortas of apoE −/ − mice cotreated with empagliflozin. Finally, in vitro studies in human aortic endothelial cells and macrophages showed that empagliflozin inhibited leukocyte-endothelial cell interactions and release of proinflammatory chemokines. Conclusions: Pharmacological inhibition of SGLT-2 by empagliflozin inhibits AAA formation. SGLT-2 inhibition might represent a novel promising therapeutic strategy to prevent AAA progression. Abstract : Supplemental Digital Content is available in the text.